Assessing fire Emeregency Response Procedure (ERP) on residential college in Universiti Teknologi MARA Shah Alam / Muhammad Izzul Islam Jaafar - Jaafar, Muhammad Izzul Islam (Faculty of Architecture, Planning and Surveying, 2014)
Fire Emergency Response Procedure is one of the important knowledge and information that required for all occupants to have if they are staying in a building. In a building, the percentage to having a emergencies cases is high if we referred to cases before. The management, fire brigade and also the occupants itself needs to have responsibility in order to against real fire situation. This study aim is to make a survey on Fire Emergency Response Procedure (ERP) on residential college in UiTM Shah Alam. With this aim, we can find the actual level of knowledge of the students towards Fire ERP that might be used in real fire situation if it is happens in their residential college. In this research, the researcher are going to identify the fire emergency response procedure (ERP) in residential college in UiTM Shah Alam. The researcher also tend to study on students awareness towards fire emergency response procedure (ERP)requirements at their residential college. After done with both objective required above, the researcher will recommend the action that should be taken in increasing the students awareness towards fire emergency response procedure (ERP). The case study we have chosen is residential college such as Delima, Teratai and also Perindu. 60 questionnaires have been distributed to the students staying in the residential college. The result were then be analyzed as concluded in chapter four and chapter five.